Shaping Teaching Practice in Malaysia A System's View - Tee, Meng Yew; Boon Kheng, Nicholas Lee (Education in South East Asia, 2024)
What teachers do in the classroom is one of the most significant school-based factors in shaping student learning. Yet the classroom is often referred to as a 'black box' because there's so little we know about what actually happens there. This book provides insights into the 'black box' by describing and then comparing classroom practices in Malaysia's national public school system and that of a unique subsystem situated within it. Through analysis of hundreds of hours of classroom video data, as well as interviews, this book goes on to identify and discuss the forces that shape teachers' classroom practices from across the ecological system. What emerged were nuanced insights of how tightly and loosely coupled forces within the centralised Malaysian national system shaped these teachers' classroom practices, that are illustrated in multiple case studies. Additionally, this volume uncovers micro-disruptions to some tightly-coupled forces within the system that could begin to change teachers' thinking about their classroom practice. These insights will be of interest to international and comparative education researchers, education policy makers and education professionals as well as anyone who has ever asked the question "Why do teachers do what they do in their classrooms?